La metrica accentuale di Franco Fortini. Teoria e prassi - Giuntini, Costanza (L’ospite ingrato, 2022)
The purpose of this article is to deepen Franco Fortini’s considerations about the free metrics, starting with his theoretical writings on this subject. The poet’s reflections on metrics do not emphasizes only the aesthetic and literary aspect, but also the sociological one. Fortini firmly believes that metrics is a way to recreate a shared view with the readers. One of the most fascinating theories by Fortini concerns the existence of a new kind of metrics, which began to spread during the Forties, called “metrica accentuale”, based on ictus isochrony. The analysis of some poems written by Fortini was fundamental to verify this hypothesis and to understand the nature of this new metrics. The analysis has revealed that metrics based on accent patterns is less binding than the traditional one. This is because it deals with the rhythmic aspect and also with the subjectivity of each reader. These features involve the equivocation of the readings based on “metrica accentuale”, but this is not an issue against such theory. On the contrary this is the strength of the theory because the flexibility of this metrics enables a greater involvement of the readers. According to Fortini’s remarks the public’s participation is crucial for the future of Poetry.